FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN BERBELANJA PADA GLOW SUPERMARKET DI BANJARMASIN - Defin Shahrial Putra; Abdurrahim - (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
Abstract, The advancement of retail business in Indonesia is caused by the growth from manufacturer venture and market opportunity is quite large due to the influence of rapid economic conditions of society. The more minimart and supermarket that are close by society, the more it have crucial roles on daily life. Glow supermarket is one of supermarket that has strategic location in Banjarmasin and provides various daily needs for locals. Purpose of this research is to know and analyze the influence of product factors, locations, parking areas, prices, promotions and services whether jointly or partially on consumer decisions to go shopping in Glow supermarket. Population of the research is society from Kelurahan Sungai Miai which has 17.569 people. By purposive sampling technique, there were 100 people used double linier regression (regresi linier berganda) analysis. Result of the research shows joint (stimulant) of product factors, locations, parking areas, prices, promotions and services giving effects on consumer decisions to go shopping in Glow Supermarket. By partially, product factors, locations, prices, promotions and services are giving effects significantly on consumer decisions to go shopping in Glow Supermarket. In other hand, parking area factor is having smallest effect on consumer decisions to go shopping on it. Meanwhile, the most dominant factor is services.